HONTOLOGY: A MULTILINGUAL ONTOLOGY FOR THE ACCOMMODATION SECTOR IN THE TOURISM INDUSTRY - Chaves, Marcirio (2012)
Ontologies have been used to support both web agents reasoning and human decision making. However, ontology development is a new area and for some knowledge domains they are still rare. Although ontologies had been developed in the context of Semantic Web, it is the Web 2.0 content that is actually pervasive on the web. One of the properties of this content is to be multilingual, which requires multilingual resources to deal with it. Online reviews are examples of multilingual texts provided by products and services consumers. This paper presents a multilingual ontology for the accommodation sector. As a result, we deliver Hontology, a freely available domain-speciﬁc ontology. Hontology reuses concepts of other vocabularies such as Dbpedia.org and Schema.org. It is useful for a wide range of applications within the accommodation sector, including ontology-based information extraction, text annotation and information visualisation